Sistem Rekomendasi Makanan Kucing Menggunakan Metode Content-Based Filtering - Kumarahadi, Brigitta Melati; Kumarahadi, Yovita Kinanti; Ridhwanullah, Dziky (Jurnal Kridatama Sains dan Teknologi, 2025)
Cats are popular pets because they have cute behavior and adorable physical appearance. Caring for cats does require extra attention, especially when feeding them. Providing food that suits their needs is very important for optimal growth and preventing various health problems. The cat food recommendation system is the right solution for cat owners to choose food that suits their cat's needs. A recommendation system is a system designed to help users get recommendations for items that are relevant and useful. Content based filtering is a recommendation system that provides suggestions based on user preferences for several items, including age, variant, brand, taste, size and price. The data used is cat food products with the brands Whiskas, Cat Choize, Me-O, and Royal Canin at the Pet Shop Colomadu. The recommendation value is calculated based on the cosine similarity value between two items. System testing is carried out using functionality testing (blackbox) and validity testing. The results of functionality testing show that the system can function well. The results of validity testing show that the system is valid and can be used appropriately. It can be concluded that the cat food recommendation system using the content-based filtering method can be used to recommend the right cat food